2017
DOI: 10.1155/2017/6823917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuropeptide Y on Stem Cells and Their Potential Applications in Disease Therapy

Abstract: Neuropeptide Y (NPY), a 36-amino acid peptide, is widely distributed in the central and peripheral nervous systems and other peripheral tissues. It takes part in regulating various biological processes including food intake, circadian rhythm, energy metabolism, and neuroendocrine secretion. Increasing evidence indicates that NPY exerts multiple regulatory effects on stem cells. As a kind of primitive and undifferentiated cells, stem cells have the therapeutic potential to replace damaged cells, secret paracrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 117 publications
1
15
0
Order By: Relevance
“…Of note, UCP2 is associated with the NPY/AgRP hypothalamic neurons, its expression being crucial for activation of these neurons . Unlike CART, POMC, and AgRP, which are expressed exclusively in the hypothalamus, NPY is one of the most abundant neuropeptides and shows a wide distribution within the central nervous system . Indeed, in addition to food intake, NPY is implicated in other processes including regulation of circadian rhythm, energy metabolism, cardiovascular function, and neuroendocrine secretion .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, UCP2 is associated with the NPY/AgRP hypothalamic neurons, its expression being crucial for activation of these neurons . Unlike CART, POMC, and AgRP, which are expressed exclusively in the hypothalamus, NPY is one of the most abundant neuropeptides and shows a wide distribution within the central nervous system . Indeed, in addition to food intake, NPY is implicated in other processes including regulation of circadian rhythm, energy metabolism, cardiovascular function, and neuroendocrine secretion .…”
Section: Discussionmentioning
confidence: 99%
“…32 Indeed, in addition to food intake, NPY is implicated in other processes including regulation of circadian rhythm, energy metabolism, cardiovascular function, and neuroendocrine secretion. 32 Since we isolated the total mouse brain RNA, measured NPY mRNA was not specifically from hypothalamic areas and may reflect nonhypothalamic sources of this neurotransmitter. Moreover, in this study, changes in NPY were not associated with differences in mRNA expression of the final effectors of food intake, such as orexin and PMCH in irisin-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY actions might also include preservation of a stable microenvironment in the bone marrow niche thereby securing the pool of immune cell progenitors [ 179 , 180 ]. The stem cell regulatory functions of NPY could highlight the potential of this peptide as a modulatory supplement in stem-cell-based therapeutic regimens for a range of diseases e.g., osteoporosis (reviewed by Peng et al [ 181 ]). Regarding OA, studies of the impact of NPY on the immunologic and degradative mechanisms are lacking and predominantly indicate that NPY participates in pain mechanisms [ 76 ].…”
Section: Effects Of the Neuroendocrine Systemmentioning
confidence: 99%
“…It is produced by nerve endings, and acts as a critical molecule in the interactions between nerves and the osseous system through central- and peripheral-mediated pathways[ 4 , 5 ]. NPY can maintain the homeostases of bone, blood vessels, and immune system via different NPY receptors[ 6 , 7 ]. Previous studies have indicated that NPY can stimulate proliferation, promote osteoblastic differentiation, and prevent apoptosis of bone marrow mesenchymal stem cells (BMSCs) though Y1R[ 8 ].…”
Section: Introductionmentioning
confidence: 99%